Study of element concentrations in blood serum of patients receiving parenteral nutrition using total reflection X-ray fluorescence analysis - Monika Pierzak-Stępień; Aldona Kubala-Kukuś; Dariusz Banaś; Ilona Stabrawa; Jolanta Wudarczyk-Moćko; Karol Szary; Monika Biernacka; Milena Piotrowska; Dariusz Pasieka; Natalia Wojtaś; Andrzej Dąbrowski; Stanisław Głuszek (PLoS ONE, 2026)
Total reflection X-ray fluorescence (TXRF) analysis was used to determine element concentrations in blood serum samples of patients receiving parenteral nutrition. The concentrations of elements were measured in the serum samples two times, namely in the first day (measurement I) of the treatment and on the seventh day (measurement II) after nutrient supplementation. For comparison purposes, also serum samples of 50 patients without nutritional disorders, admitted to a planned cholecystectomy (surgical procedure of the gall bladder removal), were analyzed and treated as the control group. Descriptive statistics of measured concentrations of P, S, Cl, K, Ca, Cr, Fe, Cu, Zn, Se, and Br were determined both for the studied and control groups. Statistical analysis of the results concentrates on verifying the type of element concentration distributions. Next, the comparison of element concentration between groups of women and men was done. Parenteral nutrition resulted in a significant increase in supplemented Se and a decrease in Cu concentrations between measurement I and II. Parametric as well as nonparametric approaches were applied to verify the hypothesis. Additionally, it was found out that for some elements differences between the studied and control groups can be observed (P, S, Ca, Fe, Cu, Zn, Se, Br). The analyses were also performed taking into account the gender of the patients. Correlation coefficients were calculated for the studied and control groups as regards the determined elements. It was observed that in all groups positive correlations were obtained between S and Ca, and for Zn and Se. In studied and control groups a negative correlation between Ca and Cr was obtained. This paper discusses also prediction of trace element concentrations following seven days of parenteral nutrition therapy, based on the knowledge of various anthropometric, biochemical and immunological parameters describing the patient’s condition. The procedure is discussed for Br concentration.